Youtube as a Learning Tool for Pottery Craftsmen in Mayong District, Jepara Regency - Darsin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to find out how pottery craftsmen in Jepara district use YouTube as a learning tool and also to find out what are the advantages and disadvantages of YouTube as a learning tool for pottery craftsmen in Jepara district. This research was conducted for 2 months, namely January 2023 - February 2023 which was carried out on pottery craftsmen in Jepara district. The population of this study were pottery craftsmen in Jepara district. This type of research uses qualitative methods based on new media theory. Primary data was obtained by direct interviews while secondary data was obtained from literature studies of books or internet media. The results of the study show that YouTube is useful as a learning tool for pottery craftsmen in Jepara district. This research also proves that there are characteristics of YouTube which are based on utilization for its users according to the needs of the respondents from the resource persons regarding the advantages of YouTube as a learning tool which lean towards its advantages, namely the effectiveness of YouTube as a learning tool.